2014
DOI: 10.1371/journal.pone.0085054
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Docosahexaenoic Acid Levels Are Associated with Fetal Insulin Sensitivity

Abstract: BackgroundArachidonic acid (AA; C20∶4 n-6) and docosahexaenoic acid (DHA; C22∶6 n-3) are important long-chain polyunsaturated fatty acids (LC-PUFA) in maintaining pancreatic beta-cell structure and function. Newborns of gestational diabetic mothers are more susceptible to the development of type 2 diabetes in adulthood. It is not known whether low circulating AA or DHA is involved in perinatally “programming” this susceptibility. This study aimed to assess whether circulating concentrations of AA, DHA and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 42 publications
2
41
1
1
Order By: Relevance
“…In the first study, cord blood levels of the n-6 FA 319 GLA, but not ARA, LA, DHA, or EPA were inversely associated with 320 fasting insulin and HOMA-IR at 7 y [57]. In the second study, cord 321 blood DGLA was inversely associated with the glucose/insulin ratio 322 and DHA and ALA levels were inversely associated with proinsulin 323 levels [68]. A higher PUFA/SFA intake ratio during pregnancy was Parameter estimate from mentioned statistical model, +, positive value (increase in outcome); À, negative value (decrease in outcome); null, no association.…”
Section: Results Of Included Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the first study, cord blood levels of the n-6 FA 319 GLA, but not ARA, LA, DHA, or EPA were inversely associated with 320 fasting insulin and HOMA-IR at 7 y [57]. In the second study, cord 321 blood DGLA was inversely associated with the glucose/insulin ratio 322 and DHA and ALA levels were inversely associated with proinsulin 323 levels [68]. A higher PUFA/SFA intake ratio during pregnancy was Parameter estimate from mentioned statistical model, +, positive value (increase in outcome); À, negative value (decrease in outcome); null, no association.…”
Section: Results Of Included Studiesmentioning
confidence: 93%
“…Only six studies examined the associations between PUFAs in 414 early life and measures of insulin sensitivity. The results of these 415 studies suggest a beneficial effect of PUFAs: DHA supplementation 416 in pregnancy led to lower insulin levels in cord blood in a trial in 417 47 women [37], and observational studies reported inverse associ-418 ations between DHA, ALA, and DGLA levels with proinsulin in cord 419 blood[68]; between GLA levels in cord blood and HOMA-IR at 7 y 420[57]; and between maternal PUFA intake and infant insulin levels421 [48]. This potential beneficial effect on insulin sensitivity was not 422 observed in a meta-analysis of n-3 FA intervention studies in adults 423 [89].…”
mentioning
confidence: 99%
“…These PUFAs must come from the diet of the mother and their amount and the n-3/n-6 balance may well be one of the “stressors” that drives the pathogenesis of GDM [7, 8]. There is already a good deal of evidence from non-pregnant humans and experimental animal models showing that dietary fatty acid composition strongly influences both insulin secretion and sensitivity [911].…”
Section: Introductionmentioning
confidence: 99%
“…Kolejne badanie kliniczne wykazało, iż obniżenie stężenia estrogenów, obserwowane u ciężarnych z cukrzycą, może stanowić przyczynę niedoborów omega-3. Estrogeny stymulują bowiem konwersję kwasu alfa linolenowego do DHA i EPA [15]. Przeprowadzone do tej pory badania pozwalają na wysunięcie wniosku, iż być może odpowiednia suplementacja kwasów omega-3 u kobiet ciężarnych pozwoli na ograniczenie u dzieci zjawiska powstawania insulinooporności, a co za tym idzie -zmniejszy ryzyko rozwoju cukrzycy typu 2 w wieku dorosłym.…”
Section: Wewnątrzmaciczna śMierć Płoduunclassified